UPAYA PELESTARIAN TARI DAMPIENG SALENDANG DI KECAMATAN KOTO XI TARUSAN PESISIR SELATAN - Maulidya, Rizki Iasha; Nerosti, Nerosti (SENDRATASIK UNP, 2019)
Abstract This study aims to describe the efforts to preserve Dampieng Salendang dance in Koto XI Tarusan district. This type of research was qualitative that produced descriptive analytical data. These types of data used both primary and secondary data. The main instrument in this study was the researcher and it was assisted by using supporting instruments such as stationery, photo camera and video camera. Techniques ofdata collection were carried out bytaking literature study, involved observation, interviews and documentation. Techniques of data analysiswere done by collecting, describing and making data conclusions. The result shows that theDampieng Salendang dance is a traditional dance that is only performed on a wedding party for the descendants of the princesses in Koto XI Tarusan district. Its development is halted along with the extinction of the royal system in Indonesia. So, an effort is made to preserve theSalendang Dampieng dance. The efforts that have been made in this study are: (1) Training and (2)Dance Performance of Dampieng Salendangin Nagari Nanggalo, Koto XI Tarusan district. The steps for conducting the training are: (a) Making an agreement with the owner of Dance or daughter of Puteri Darna. (b) Arranging the movements of theDampieng Salendang dancein the form of welcoming marapulai, (c) Training of theDance at the Dampieng Pucuak SalendangRabuang Studio. Meanwhile, theDampieng Salendang danceis Performed at the Nagari Nanggalo community wedding party in Koto XI Tarusan district on August 18, 2019. The conclusion of the study proves that theDampieng Salendang dancecan now be accepted by the community in the form of preservation which is carried out in the form of training and performances, which can be displayed and used for a community wedding party event generally in the Koto XI Tarusan district eventhough they are not the descendants of Raja Tarusan. Keywords: Conservation effort,dance Dampieng Salendang, Puti-puti descendant, Koto XI Tarusan